KEPUTUSAN PENDANAAN DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN DENGAN KEBIJAKAN DEVIDEN SEBAGAI PEMODERASI - Sari Rahayu; Poppy Meilina (STIE Mahardhika, 2023)
This research was conducted to examine the effect of funding decisions and profitability on company value with a dividend policy as moderation in property and real estate companies listed on the Indonesia Stock Exchange in 2017-2021. The population in thisstudy are all property and real estate companies listed on the IDX in 2017-2021, there are 62 companies. The technique in determining the sample using purposive sampling method. The sample in this study were 6 companies. In this study using annual data with a total of 32 data samples and using SPSS 26 as a statistical test tool. The results of this study indicate that funding decisions have no effect on firm value and profitability has a positive effect on firm value. Furthermore, dividend policy is not able to moderate funding decisions but is able to moderate the effect of profitability.